Sustainable Cities and Society - Sustainable Cities and Society (Elsevier, 2026)
Sustainable Cities and Society (SCS) is an international journal focusing on fundamental and applied research aimed at designing, understanding, and promoting environmentally sustainable and socially resilient cities.
FI 1.92
Q1
Keywords: Earth; Space & Environmental Sciences; Sustainable Development; Ciencias de la tierra; Desarrollo sustentable; Acuerdos transformativos; Transformative agreements; Ciudades inteligentes; Fuentes de energía; Calidad del aire; Cambio climático; Aguas residuales